Anatomia e fisiologia de clones de Coffea canephora em condições de cerrado - Matos, Nagla Maria Sampaio de (2016)
Hydric stress is one of the abiotic factors that most hinder the development and productivity of coffee in Brazil. Therefore, we aimed with the present study to identify anatomic and physiological characteristics in clones of Coffea canephora that can be used in the pre-selection of plants for genetic breeding for tolerance to draught. We also sought to identify, among the studied clones, those that group most of these characteristics. To conduct this study, we used seven clones of Coffea canephora (1, 3, 7, 8, 11, 12 and 13) with three years of age. The plants underwent suspension of irrigation for a period of 60 days in 2015, for standardization of the flowering. At the end of this period, two days and three months after the return of irrigation, we conducted physiological and anatomic evaluations. The results allowed us to infer that the plants subjected to suspension of irrigation, under cerrado conditions, activated adaptation and/or survival mechanisms because of the environment to which they were exposed. The potential characteristics to be used in the pre-selection of coffee plants for genetic breeding were: cuticle, adaxial epidermis, phloem and palisade parenchyma thickness, as well as hydric behavior, water use efficiency and leaf area index. The clones of number 1, 12 and 13 presented most characteristics related to tolerance for drought between those studies.